2020
DOI: 10.1158/1541-7786.mcr-20-0282
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Receptor Beta Induces a Tumor-Suppressive Program in Anaplastic Thyroid Cancer

Abstract: The thyroid hormone receptor beta (TRb), a key regulator of cellular growth and differentiation, is frequently dysregulated in cancers. Diminished expression of TRb is noted in thyroid, breast, and other solid tumors and is correlated with more aggressive disease. Restoration of TRb levels decreased tumor growth supporting the concept that TRb could function as a tumor suppressor. Yet, the TRb tumor suppression transcriptome is not well delineated and the impact of TRb is unknown in aggressive anaplastic thyro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 47 publications
2
45
0
Order By: Relevance
“…PI3K signaling fuels cancer progression by stimulating cell survival, proliferation, and migration. We previously demonstrated that TRβ inhibits SW1736 proliferation in charcoal-stripped media, an observation that was dependent upon T 3 stimulation (15). To achieve phenotypic confirmation of our sequencing results, we challenged our engineered cells in full serum (10%) media with or without additional 10 nM T 3 to measure a functional consequence of PI3K inhibition.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…PI3K signaling fuels cancer progression by stimulating cell survival, proliferation, and migration. We previously demonstrated that TRβ inhibits SW1736 proliferation in charcoal-stripped media, an observation that was dependent upon T 3 stimulation (15). To achieve phenotypic confirmation of our sequencing results, we challenged our engineered cells in full serum (10%) media with or without additional 10 nM T 3 to measure a functional consequence of PI3K inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…Previously published RNA-seq data was used to determine expression levels of genes within the PI3K pathway (15). Construction of the PI3K signaling genes of interest for our study was based on the curated IPA pathway gene set.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations